Children adjust behavior in novel social environment to reflect local prosocial norms inferred from brief exposure - Kari Britt Schroeder; Laura Nelson Darling; Peter R. Blake (PLoS ONE, 2025)
Stark cultural variation in prosocial behavior, as elicited with economic experiments, is evident despite the high mobility of humans. Conformity to local norms has been posited to play an integral role in the maintenance of this variation. Experiments suggest that adults indeed rapidly infer pro- and antisocial norms in new or altered social environments and adjust their behavior to reflect the inferred norms. Studies of the ontogeny of prosocial behavior show that by middle childhood, children’s prosocial behavior conforms to that of local adults. Furthermore, by this stage, children are susceptible to the manipulation of explicit normative information. However, their propensity to extract or infer normative information from the environment and change their behavior accordingly has not been investigated. Here, we assess whether children 1) rapidly infer local prosocial norms in a novel, realistic social environment, 2) extend these inferences to norms for unobserved behaviors, and 3) alter their behavior in the novel environment to align with the inferred norms while still 4) maintaining their baseline prosocial behavior outside of the novel environment. We used questionnaires to measure children’s perceived pro- and antisocial descriptive norms in their Own Neighborhoods as well as in a novel “Neighborhood X,” to which they were introduced via a slideshow. Norms for Neighborhood X diverged drastically dependent upon which slideshow they witnessed (Prosocial or Antisocial condition), a result robust to the exclusion of questions about norms for behaviors observed in the slideshow. Children’s perceptions of prosocial norms in their Own Neighborhoods predicted their prosocial behavior (Dictator Game) in their Own Neighborhood. Moreover, even though information about giving behavior was not presented in the slideshow, inferred norms for Neighborhood X predicted children’s prosocial behavior in that neighborhood as well. These changes in prosocial behavior were transitory and specific to Neighborhood X; prosocial behavior in a separate “Helping Task” was best predicted by prosocial norms within the children’s Own Neighborhoods. Our results are consistent with the hypothesis that humans have a propensity to rapidly infer and conform to local prosocial norms, thus maintaining group differences in prosocial behavior, and further indicate that this propensity is in operation by middle childhood.